Association Between Waist Circumference and the Prevalence of (Pre) Hypertension Among 27,894 US Adults - Sun, Jin-Yu; Hua, Yang; Zou, Hua-Yi-Yang; Qu, Qiang; Yuan, Yue; Sun, Guo-Zhen; Sun, Wei; Kong, Xiang-Qing (Frontiers in Cardiovascular Medicine, 2021)
Aims This study aimed to investigate the association between waist circumference and the prevalence of (pre) hypertension. Methods Cross-sectional data from the 2007-2018 National Health and Nutrition Examination Survey were analyzed. The historical trend of abdominal obesity was assessed by the Cochran-Armitage trend test. After preprocessed by the multiple imputation strategy, we used generalized additive models to assess the association of waist circumference with systolic/diastolic blood pressure and performed correlation analysis by the Spearman correlation coefficient. Moreover, we used multivariable logistic regression (non-adjusted, minimally-adjusted, and fully-adjusted models), restricted cubic spline, and sensitivity analysis to investigate the association between waist circumference and (pre) hypertension. Results A total of 27,894 participants were included in this study. In the fully-adjusted model, waist circumference was positively associated with (pre) hypertension with odds ratios (95% confidence intervals) of 1.28 (1.18-1.40) in the young group and 1.23 (1.15-1.33) in the old group. Restricted cubic spline showed a higher prevalence of (pre) hypertension with the increase of waist circumference. In the subgroup analysis, waist circumference showed a robust trend across all BMI categories with odds ratios (95% confidence intervals) of 3.33 (1.29-8.85), 1.35 (1.17-1.57), 1.27 (1.13-1.41), and 1.09 (1.01-1.17) in underweight, normal weight, overweight, and obese individuals, respectively. Conclusion This study highlighted waist circumference as a significant biomarker to evaluate the risk of (pre) hypertension. Our results supported the measure of waist circumference regardless of BMI when evaluating the cardiometabolic risk related to fat distribution.